The perception of income taxation on risky investments: An experimental analysis of different methods of loss compensation - Martin Fochmann; Dirk Kiesewetter; Abdolkarim Sadrieh (Arbeitskreis Quantitative Steuerlehre (arqus), 2009)
We analyze the effect of income taxation with limited loss deduction on investment decisions. An experiment with five treatments was conducted, one without taxation as a reference and four with taxation and limited loss compensation. The participants' task was to repeatedly choose one out of two risky investment opportunities. Earnings from the experiment depended on the payoffs of the participant's investments. Our results reveal that subjects do not only look at gross payoffs but also take taxes into account in their decisions. The experimental setup made sure that a rational participant who correctly perceives the effect of the different loss offset rules would take exactly the same decisions with and without taxation. Nevertheless, we find out that individuals tend to overestimate the value of loss compensation rules which offer less than a complete loss offset.
Keywords: 330